2020
DOI: 10.1002/cbin.11371
|View full text |Cite
|
Sign up to set email alerts
|

miR‐16 exhibits protective function in LPS‐treated cardiomyocytes by targeting DOCK2 to repress cell apoptosis and exert anti‐inflammatory effect

Abstract: This study aims to investigate the effects of microRNA (miR)‐16/dedicator of cytokinesis 2 (DOCK2) on myocarditis. The differences in the expression of genes in acute myocarditis were filtered out across Gene Expression Omnibus (GEO) database. Myocarditis cell model was established by lipopolysaccharide (LPS) stimulation in cardiomyocytes. The association between miR‐16 and DOCK2 was predicted by bioinformatics software and confirmed by dual‐luciferase assay. Polymerase chain reaction and western blot analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…MiR-16 has also been found to have suppressive effects on inflammation in some diseases. [18][19][20][21] Our study found that, similar to CAI, miR-16 expression was decreased in sepsis-induced CHF patients. In addition, miR-16 expression in AC16 cells decreased with increasing LPS concentration, suggesting that miR-16 might be an inflammatory response resistance factor.…”
Section: Caif and Mir-16 Overexpression Suppressed Lps-induced Cardiomyocyte Apoptosissupporting
confidence: 55%
“…MiR-16 has also been found to have suppressive effects on inflammation in some diseases. [18][19][20][21] Our study found that, similar to CAI, miR-16 expression was decreased in sepsis-induced CHF patients. In addition, miR-16 expression in AC16 cells decreased with increasing LPS concentration, suggesting that miR-16 might be an inflammatory response resistance factor.…”
Section: Caif and Mir-16 Overexpression Suppressed Lps-induced Cardiomyocyte Apoptosissupporting
confidence: 55%
“…Analysis by the GSE35182 and GSE53607 databases showed that DOCK2 was significantly upregulated in myocarditis. And increased expression of DOCK2 was positively correlated with pro-inflammatory factors such as IL-6 and TNF-α ( Wang et al, 2020 ). The study revealed a correlation between miR-16 and DOCK2, with miR-16 expression significantly down-regulated in LPS-induced myocarditis.…”
Section: Role Of Dock2 In Diseasesmentioning
confidence: 99%
“…The study revealed a correlation between miR-16 and DOCK2, with miR-16 expression significantly down-regulated in LPS-induced myocarditis. Then miR-16 depletion by inhibitors was followed by an elevated expression of DOCK2 at both mRNA and protein levels ( Wang et al, 2020 ). The miR-16 inhibitor promoted LPS-induced cardiomyocyte apoptosis and attenuated the effect of the miR-16 inhibitor on cardiomyocytes by inhibiting DOCK2 expression, and these phenomena could also be reversed by miR-16mimic treatment ( Wang et al, 2020 ).…”
Section: Role Of Dock2 In Diseasesmentioning
confidence: 99%
See 2 more Smart Citations